Post-submission changes to prespecified statistical analysis plans. (21st September 2022) - Islam, Nazrul; Cole, Tim J; Ross, Joseph S; Feeney, Timothy; Loder, Elizabeth
Abstract : These plans are fundamental to research integrity, but not immutable